On poetry and poets - Eliot, T. S. (Farrar, Straus and Giroux, 2009)
Seven essays on poetry, with definitions on the mind of the creative writer, and nine essays on poets - Virgil, Sir John Davies, Milton, Johnson, Byron, Goethe, Kipling, and Yeats.
Keywords: Aufsatzsammlung; 1957; Poetry; Literatur; Versdichtung